The Effect of Value Perception and Satisfaction Towards Loyalty of Gojek Customers in Yogyakarta - Putri Sundarinigsih; Kamarudin Othman; Nonik Kusuma Ningrum (Universitas Tidar, 2021)
This study illustrates that Gojek customer loyalty in Yogyakarta remains significant even though it is still in tight business competition. This means that Gojek management must maintain and increase customer loyalty under any circumstances. In addition, the results of this study provide insights for academics in studying and developing research in the field of marketing, especially on the topic of customer loyalty. This study illustrates that Gojek customer loyalty in Yogyakarta remains significant even though it is still in tight business competition. This means that Gojek management must maintain and increase customer loyalty under any circumstances. In addition, the results of this study provide insights for academics in studying and developing research in the field of marketing, especially on the topic of customer loyalty.